A study of a distributed function engine control system with a serial communication network. (4th August 2014) - Harata, Y.; Nishimura, Y.; Kirnura, M.; Nagase, H.; Ishii, K.; Takigawaj, M.
Engine control systems have become more complex in recent years, requiring higher speed and more flexible control. We therefore made a trial distributed function engine control system to control every combustion cycle of each cylinder. This engine control system is constructed with six controllers: two of them are used for sensor control, three for actuator control, and the rest is used for large data processing such as model identification of optimal control and parameter decision of learning control. These six controllers are connected with a new serial communication network which has a ring type structure (the data transfer rate is 1 Mbits/sec). The system is applied to engine idle speed control or lean burn. The deviation of engine speed is less than 15 rpm when the engine idle speed is 450 rpm and the air–fuel ratio is 18. The result indicates the effectiveness of distributed function engine control system.